'GA 03564‐12E6': A High‐Yielding Soft Red Winter Wheat Cultivar Adapted to Georgia and the Southeastern Regions of the United States. Issue 2 (27th April 2017) - Johnson, Jerry W.; Chen, Z.; Buck, James W.; Buntin, G.D.; Babar, Md A.; Mason, Richard E.; Harrison, Stephen A.; Murphy, J. Paul; Ibrahim, Amir M. H.; Sutton, Russell L.; Simoneaux, Bryan E.; Bockelman, Harold E.; et al.
Abstract : Soft red winter wheat (SRWW) ( Triticum aestivum L.) is a major crop in the southeastern region of the United States and in Georgia. Although wheat acreages have been decreasing in Georgia and the SE region in recent years, more than 100, 000 ha were grown to SRWW in 2015. Newly released cultivars must have high yield potential, excellent resistance levels to predominant diseases and insects, and good quality to capture and maximize regional market value. One objective of the SRWW breeding program at the University of Georgia (UGA) is to develop and release SRWW cultivars adapted to the SE wheat region with high yield, quality, and pest resistance. 'GA 03564‐12E6' (Reg. No. CV‐1122, PI 677366) SRWW was developed by the UGA small grains breeding program and the SUNGRAINS cooperative and released by the UGA College of Agricultural and Environmental Sciences and licensed to Limagrain Cereal Seeds as L11544 in 2015. GA 03564‐12E6 was released primarily for its wide adaptation to the SE region with high grain yield, excellent Hessian fly resistance, and excellent grain volume weight. Additionally, GA 03564‐12E6 has good resistance to races of leaf rust and stripe rust predominant in Georgia and the SE United States. It has good resistance to powdery mildew (caused by Blumeria graminis f. sp. tritici ) and Soil‐borne wheat mosaic virus and has acceptable SRWW milling and baking quality. However, it is susceptible to Fusarium head blight (FHB) or scab [caused by Fusarium graminearum Schwabe; teleomorph Gibberella zeae (Schwein.) Petch].